Polychlorinated biphenyls modify Arabidopsis root exudation pattern to accommodate degrading bacteria, showing strain and functional trait specificity - Rolli, Eleonora; Ghitti, Elisa; Mapelli, Francesca; Borin, Sara (Frontiers in Plant Science, 2024)
The importance of plant rhizodeposition to sustain microbial growth and induce xenobiotic degradation in polluted environments is increasingly recognized. Here, the 'cry-for-help' hypothesis, consisting in root chemistry remodeling upon stress, was investigated in presence of polychlorinated biphenyls (PCBs), highly recalcitrant and phytotoxic compounds, highlighting its role in reshaping the nutritional and signaling features of the root niche to accommodate PCB degrading microorganisms. Arabidopsis exposure to 70 µM PCB-18 triggered plant detrimental effects, stress-related traits and PCB-responsive gene expression, reproducing PCB phytotoxicity. The root exudates of plantlets exposed for 2 days to the pollutant were collected and characterized through untargeted metabolomics analysis by LC-MS. Principal component analysis disclosed a different root exudation fingerprint in PCB-18-exposed plants, potentially contributing to a 'cry-for-help' event. To investigate this aspect, the five compounds identified in the exudate metabolomic analysis (i.e. scopoletin, N-hydroxyethyl-β-alanine, hypoxanthine, L-arginyl-L-valine and L-seryl-L-phenylalanine) were assayed for their influence on the physiology and functionality of the PCB degrading strains Pseudomonas alcaliphila JAB1, Paraburkholderia xenovorans LB400 and Acinetobacter calcoaceticus P320. Scopoletin, which relative abundance decreased in PCB-18-stressed plant exudates, hampered the growth and proliferation of strains JAB1 and P320, presumably due to its antimicrobial activity, and reduced the beneficial effect of Acinetobacter P320, that showed a higher degree of growth promotion in the scopoletin-depleted mutant f6'h1 compared to Arabidopsis WT plants exposed to PCB.Nevertheless, scopoletin induced the expression of the bph catabolic operon in strain JAB1 and LB400. The primary metabolites hypoxanthine, L-arginyl-L-valine and L-seryl-L-phenylalanine, that increased in relative abundance upon PCB-18 stress, were preferentially used as nutrients and growth stimulating factors by the three degrading strains and showed a variable ability to affect rhizocompetence traits like motility and biofilm formation. These findings expand the knowledge on PCB-triggered 'cry-for-help' and its role in steering the PCB degrading microbiome to boost the holobiont fitness in polluted environments.